2013
DOI: 10.3390/molecules18044267
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Methyl Jasmonate-Induced Triterpenoid Production in the Medicinal Herb Centella asiatica (L.) Urban

Abstract: Centella asiatica is an important source of biologically active pentacyclic triterpenoids. The enhancement of the biosynthesis of the centellosides by manipulation of associated metabolic pathways is receiving much attention. Jasmonates play critical roles in plant metabolism by up-regulating the expression of genes related to secondary metabolites. Here, we investigated the effect of methyl jasmonate (MeJa) in C. asiatica through targeted metabolomic profiling of asiaticoside and madecassoside as well as thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…In Panax notoginseng cell cultures, elicitation with jasmonate derivates during the early exponential phase of growth up-regulate squalene synthase and squalene epoxidase, two common enzymes of triterpene and sterol biosynthesis, but down-regulate the sterol related cycloartenol synthase transcription, which implies that oxidosqualene can be directed from sterol to ginsenoside biosynthesis (Hu and Zhong 2008). Similar results about the decrease in free phytosterols and the increase in triterpene production were observed when MeJA was applied in the late or in the exponential phase of Centella asiatica cell suspension cultures (James et al 2013).…”
Section: Effect Of Ja Concentration and Time Of Elicitationsupporting
confidence: 82%
See 1 more Smart Citation
“…In Panax notoginseng cell cultures, elicitation with jasmonate derivates during the early exponential phase of growth up-regulate squalene synthase and squalene epoxidase, two common enzymes of triterpene and sterol biosynthesis, but down-regulate the sterol related cycloartenol synthase transcription, which implies that oxidosqualene can be directed from sterol to ginsenoside biosynthesis (Hu and Zhong 2008). Similar results about the decrease in free phytosterols and the increase in triterpene production were observed when MeJA was applied in the late or in the exponential phase of Centella asiatica cell suspension cultures (James et al 2013).…”
Section: Effect Of Ja Concentration and Time Of Elicitationsupporting
confidence: 82%
“…Likewise, it is known that exogenous JA can act as an elicitor in plants (Zhao et al 2005;Wasternack and Hause 2013). In diverse plant cell cultures, jasmonates have been used to induce the production of pentacyclic triterpenes, mainly oleanolic acid and ursolic acid (Norrizah et al 2012), as well as b-amyrin (Broeckling et al 2005), betulinic acid (Pandey et al 2015) and other triterpenes (James et al 2013). In the presence of elicitors, there is an immediate cellular response to trigger plant defense signals with increased accumulation of reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ), superoxide anions (O 2 -) and hydroxyl free radicals (HO Á ).…”
Section: Introductionmentioning
confidence: 98%
“…There were some reports on in vitro cultures of centella treated by methyl jasmonate (MJ) to improve the biosynthesis of triterpene saponins: for example, stimulation of asiaticoside production in plantlets (5) and hairy-root cultures (6) by MJ, effect of MJ on triterpene metabolisms of planlets (7), centelloside production in cells elicited by MJ (8), and metabolomic analysis of MJ-induced triterpenoid production in cells (9). However, there are no reports on the effects of salicylic acid (SA), a common chemical elicitor in plant (10), on the accumulation of madecassoside in centella cell cultures.…”
Section: Results and Conclusion: The Cell Fresh (Dry) Biomass Increamentioning
confidence: 99%
“…In order to achieve the main aim of the study, a novel way for metabolite annotation/identification was investigated and proved successful with a high degree of confidence. This approach is based on the PUTMEDID_LCeMS workflow (Brown et al, 2011), and several reports have shown the ability of this workflow in the identification of metabolites (Dunn et al, 2012;James et al, 2013;Tugizimana et al, 2014). Traditionally, metabolite identification is performed by following a fundamental approach which firstly involves the calculation of elemental composition/molecular formula (MF) of each respective m/z, followed by searching for identical MFs using online databases.…”
Section: Signatory Biomarkers and Metabolite Annotationmentioning
confidence: 99%
“…Using bacterial lipopolysaccharide (LPS) as an inducer of SAR (Coventry and Dubery, 2001), we have shown that both transcriptomics (Sanabria and Dubery, 2006;Madala et al, 2012a) and proteomics (Piater et al, 2004;Gerber et al, 2006Gerber et al, , 2008 contribute to a comprehensive understanding of activation of plant defense responses. Recently, however, it was also demonstrated that metabolomics, a science of systems biology, can be used in this regard (Beets et al, 2012;Tugizimana et al, 2012;James et al, 2013). By virtue of being the end product of most cellular metabolism, metabolites act as regulatory components of biological information flow and hence their accumulation and/or changes allow a complete snapshot of the physiological status of a cell (Sumner et al, 2003;Ryan and Robards, 2006;B€ ottcher et al, 2008;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 96%